Sexual behavior and vulnerability to AIDS: a descriptive study with perspective of prevention practice - Saldanha, Ana Alaycle W.; Carvalho, Euclismária A.B.; Diniz, Raquel F.; Freitas, Edilane S.; Félix, Shênia Maria F.; Silva, Elis Amanda A. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: the epidemic of the AIDS and pregnancy have given visibility to the youthful sexuality. One of the greatest obstacles of the injunction is the fact that public policies do not take the sexual culture of the populations and focused subpopulations into account. Objective: to describe pro files of vulnerability to STD and AIDS of adolescent students from public and private school in the city of João Pessoa - PB. Methods: participated 1.068 adolescents participated, students from public and private schools with age varying from 13 to 18 years old, 53% were women. A bio-demogra- phic questionnaire and questionnaire concerning the sexual behavior and vulnerability to AIDS were used. The results were submitted to the descrip tive statistical analyses and to the use of bivaried tests. Results: the precocious sexual initiation with older partners, and the multipartnership that increased vulnerability, aggravated by the non-systematic use of condom: always (54%), were factors in the first sexual intercourse (40%), in the last sexual relationship (29%) and confirmed by the occurrence of pregnancy were predisponent factors (7%) and abortion (4%). The perception of vulne rability to the AIDS emerges for 37% of the adolescents, being lesser for the pupils from private schools. The AIDS was seen as destination by 48% of the pupils from private education and 31% of students from state schools. The results varied for sort, sexual experience and type of school. Conclusion: the results show that two points are necessary to the effective preventive intervention: the need to extend the discussion about the cultu rally constructed masculine and feminine models and the development of studies that evaluate the consistency of the condom use to define strategies to increase its use, once higher use of condom rate does not imply a continued use.